Ambulatory pulse pressure, brain neuronal fiber integrity, and cerebral blood flow in older adults. Issue 5 (May 2019) - Tarumi, Takashi; Thomas, Binu P; Wang, Ciwen; Zhang, Li; Liu, Jie; Turner, Marcel; Riley, Jonathan; Tangella, Nikita; Womack, Kyle B; Kerwin, Diana R; Cullum, C Munro; Lu, Hanzhang; et al.
Ambulatory blood pressure (ABP) reflects the end-organ vascular stress in daily life; however, its influence on brain neuronal fiber integrity and cerebral blood flow (CBF) remains unclear. The objective of this study was to determine the associations among ABP, white matter (WM) neuronal fiber integrity, and CBF in older adults. We tested 144 participants via ABP monitoring and diffusion tensor imaging. The total level and pulsatile indices of CBF were measured by phase-contrast MRI and transcranial Doppler, respectively. Neuropsychological assessment was conducted in 72 participants. Among ambulatory and office BP measures, elevated 24-h pulse pressure (PP) was associated with the greatest number of WM skeleton voxels with decreased fractional anisotropy (FA) and increased mean diffusivity (MD). Furthermore, these associations remained significant after adjusting for age, antihypertensive use, aortic stiffness, WM lesion volume, and office PP. Radial diffusivity (RD) was elevated in the regions with decreased FA, while axial diffusivity was unaltered. The reduction in diastolic index explained a significant proportion of the individual variability in FA, MD, and RD. Executive function performance was correlated with WM fiber integrity. These findings suggest that elevated ambulatory PP may deteriorate brain neuronal fiber integrity via reduction in diastolic index.